Re-Thinking: Violence, Education, and Teachers in Indonesia - R. Nadia R. P. Dalimunthe (International Conference on Education and Language (ICEL), 2013)
Violence has become a solution for some social conflicts in Indonesia. Responding to theseissues, the government is designing a new curriculum, which is inspired byprinciples of character education. On the other hand, the system seems nonsenseif it is not supported by compatible human resources. Teachers as one of main actors in a teaching-learning process should be a concern as well. This paper is a brief reflection on violence, education, and teachers.